Peripheral Blood Mononuclear Cells Expression Levels of miR-196a and miR-100 in Coronary Artery Disease Patients. (17th November 2021) - Saadatian, Zahra; Nariman-Saleh-Fam, Ziba; Khaheshi, Isa; Mansoori, Yaser; Daraei, Abdolreza; Ghaderian, Sayyed Mohammad Hossein; Omrani, Mir Davood
ABSTRACT: As a chronic inflammatory disease, coronary artery disease (CAD) is a common cause of death worldwide. Dysregulation of microRNA expression levels in peripheral blood mononuclear cells (PBMCs) may contribute to CAD and serve as a potential diagnostic biomarker. Here, we evaluated PBMC expression of two CAD-related inflammatory miRNAs, miR-196a and miR-100, in PBMCs of CAD patients with significant stenosis (CAD, n: 72), patients with insignificant coronary stenosis (ICAD, n: 30), and controls (n: 74) and checked whether they can segregate study groups. MiRNA expression was evaluated using the standard stem-loop RT-qPCR method. MiR-196a expression was downregulated in ICAD compared to CADs and healthy groups. MiR100 expression levels were not different between groups. The receiver operating characteristic (ROC) curve analysis acquainted that miR-196a expression levels in PBMC could segregate CAD individuals or any of its clinical manifestations (i.e. unstable angina, stable angina, acute myocardial infarction) from ICADs. In conclusion, this study reported a distinct miR-196a expression pattern in PBMCs of all patient groups and recommended a biomarker potential for miR-196a in discriminating ICADs from CADs or healthy controls.